Patients' acceptance of obesity as a chronic disease: a qualitative study in Lebanon. Issue 3 (11th March 2022) - AlArab, Natally; Antoun, Jumana
Abstract : Objective: This study explores patients' acceptance of obesity as a chronic disease. Design: Cross-sectional, qualitative study using semistructured phone interviews. Setting: The study was conducted in specialty and primary care clinics from a single central tertiary hospital in Lebanon. Recruitment took place between February and March 2021. Participants and methods: 25 adult patients with overweight or obesity were interviewed and the interviews were analysed thematically. Results: Four themes emerged: (1) patients' knowledge and awareness of obesity are based on their own experience; (2) there is ambivalence or conditional acceptance of obesity as a chronic disease; and patients with overweight or obesity perceived (3) that the role of physicians in obesity management is related to complications and (4) that obesity management is as simple as eating less and exercising more. Conclusions: The study shows the studied population's ambivalence in accepting obesity as a chronic disease. Individuals with overweight or obesity considered the role of the healthcare professional in obesity conditional on morbid obesity and the presence of medical complications of obesity. Findings of this study advocate for educational campaigns about the nature of obesity as a chronic disease and the role of healthcare professionals in obesity management.